Management of chronic seromas: A novel surgical approach with the use of vacuum assisted closure therapy - Marangi, Giovanni F. (Int Wound J, 2020)
Postoperative seroma is a common complication of many surgical procedures in which anatomical dead space has been created. A particular case of lesion in which seroma occurs is the Morel‐Lavallée lesion (MLL), which is an uncommon closed soft‐tissue degloving injury that develops after high‐energy trauma or crush injury where shearing forces separate the subcutaneous tissue from the underlying fascia. The diagnostic evaluation begins with an adequate history and physical examination, followed by instrumental research with ultrasonography, computed tomography, and magnetic resonance imaging. Postoperative seromas and MLLs share a similar pathology and natural evolution as both injuries, once chronic, develop a pseudobursa; thus, the authors think that the same treatment algorithm may be suitable for both the lesions. Several strategies for the treatment of post‐surgical and post‐traumatic seromas have been described in the literature, ranging from conservative measures for acute and small injuries to surgical management and sclerotherapy for chronic and large ones. Despite some seromas resolving with conventional management, lesion recurrence is a matter of concern. The authors present their experience in the treatment of both post‐surgical and post‐traumatic chronic seromas not responsive to conservative treatments by surgical drainage of the seroma, capsulectomy, and application of vacuum‐assisted closure therapy to allow granulation tissue formation, dead spaces obliteration, and wound healing. Primary wound closure with closed suction drain placement and an elastic compression bandaging are finally performed. From 2014 to 2019, a total of 15 patients (9 females and 6 males) were treated for recurrent chronic seromas with the proposed surgical approach. Five cases were MLLs, while 10 cases were postoperative seromas. The patients were between 33 and 79 years old, and they were followed up at 4 weeks and 3 and 6 months after surgery. All 15 patients with chronic seromas not responsive to conservative treatment showed a complete resolution of the lesions with the proposed treatment approach with no evidence of lesion recurrence, proving its effectiveness.